Datos sobre los mamíferos del área aledaña a Palpan, Morelos, México - TICUL ÁLVAREZ, SERGIO; LÓPEZ FORMENT, CONRADT WILLIAM (Anales del Instituto de Biología serie Zoología, 2009)
ECOLOGICAL NOTES ARE GIVEN FOR 29 ESPECIES OF MAMMALS CAPTURED IN THE VICINITY OF PALPAN, INMNORTH WESTERN MIACATLÁN, MORELOS, FEEDING AND REPRODUCTIVE DATA OF MOST SPECIES CAPTURED ARE GIVEN. THIS AREA IS IN THE EASTERN UPPER LIMIT OF THE BALSAS, DEPRESION, AND IS LOCATED IN THE FOOTHILLS OF THE MEXICAN VOLCANIC BELT. MUSONYCTERIS HARRISON IS REPORTED FOR THE FIRS TIME FOR THE STATE.